(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The teaching of don Milani is compared with the current national educational policies and the regional educational policies of Lombardy, simultaneously highlighting its presence in current regulatory devices and the difficulty of translating it into ordinary school experiences and not just extraordinary experiences. The text illustrates some extraordinary educational realities carried out in the schools of Lombardy.